Sustainable Co‐Synthesis of Glycolic Acid, Formamides and Formates from 1, 3‐Dihydroxyacetone by a Cu/Al2O3 Catalyst with a Single Active Sites. (27th February 2019) - Dai, Xingchao; Adomeit, Sven; Rabeah, Jabor; Kreyenschulte, Carsten; Brückner, Angelika; Wang, Hongli; Shi, Feng
Abstract: Glycolic acid (GA), as important building block of biodegradable polymers, has been synthesized for the first time in excellent yields at room temperature by selective oxidation of 1, 3‐dihyroxyacetone (DHA) using a cheap supported Cu/Al2 O3 catalyst with single active Cu II species. By combining EPR spin‐trapping and operando ATR‐IR experiments, different mechanisms for the co‐synthesis of GA, formates, and formamides have been derived, in which . OH radicals formed from H2 O2 by a Fenton‐like reaction play a key role.